Current progresses in two-dimensional MXene-based framework: prospects from superficial synthesis to energy conversion and storage applications. (January 2023) - Ajmal, Zeeshan; Qadeer, Abdul; Khan, Ubaid; Bilal Hussain, Muhammad; Irfan, Muhammad; Mehmood, Rashid; Abid, Muhammad; Djellabi, Ridha; Kumar, Anuj; Ali, Hamid; Kalam, A.; Al-Sehemi, A.G.; et al.
Abstract: MXenes are regarded as a type of two-dimensional (2D) inorganic material, mainly comprising a number of transition metal carbides, nitrides, or carbonitrides atomic planes. Nevertheless, the scientific community is continuously interested in exploring and structuring the engineered-based multifunctional material for numerous applications. The MXenes-based materials in this context, have emerged as highly active compounds owing to their superior surface area, substantial interlayer spacing, highly reactive surface-active sites and surface functional group, even though, recent studies have shown significant scientific and theoretical progress related to enormous prospects in MXenes, chemical nature, robust electrochemistry and high hydrophilicity of MXenes. The role of MXenes in all kinds of strategies is still in an upgrading phase for their further improvement, and is not sufficiently summarized in the literature now. To begin with this, herein, present review article is intended to critically discuss the diversity of MXenes with respect to different composition, formulation, plasmonic, complexation, and numerous geometric and morphological aspects, along with novel construction strategies to improve their surface characteristics in all aforesaid multidimensional applications. Following that, in terms of broadening the application, this review article is envisaged to endorse the use of MXenes and their hybrid configuration in a series of emerging environmental decontamination via adsorption, photodegradation, photocatalytic fuel production via hydrogen evolution, CO2 reduction, electrocatalytic sensing, along with membrane distillation and energy storage. In addition, comprehensive information about existing obstacles and future perspectives have been addressed. Finally, an overview is succinctly summarized and discussed regarding the emerging prospects of MXenes for their potential uses in numerous research fields. At the end, it is anticipated that this review article will pave the way for the effective use of MXenes in different fields of environmental remediation, energy conversion, storage and biomedical applications as an innovative, reliable, and multifunctional material. Highlights : MXene is being discussed in this review article. Different MXenes fabrication routes are discussed in detail. Dynamics of MXene structural, chemical and optoelectronics and magnetic properties are critically evaluated. Use of MXene is discussed in detail in a wide range of scientific fields.